The Influence of the Muslim Brotherhood on Teaching Islam in American Universities - Mohamed, Mohamed Mosaad Abdelaziz (Tashwirul Afkar, 2023)
The significance of the Muslim Brotherhood in American academia lies in the academic articulation of the brothers’ discourse as the expression of modern Islam in general. As such, the discourse of a specific political group is taken as the appropriate example of modern mainstream Islam. This treatment of the brothers’ discourse has resulted in an assumption that Islam, or at least modern Islam, is essentially political. It is not surprising, therefore, that one can easily find courses that teach “Islam and Politics,” or “Islam and Democracy,” which have no parallel in courses taught on other religions. What creates this distortion is not the mere political nature of the Brothers as an organization. It is the redefinition of Islam as has been presented by the brothers’ discourse since its foundation. There, Islam is presented as a differentiated structure that mirrors the differentiated structure of the secular state. Islam is presented as a comprehensive modern system that includes a number of complementary systems: political, economic, social, educational, health, etc. that work in harmony, guided by the rational principle of maṣlaḥah, public interest. The discourse of the Brothers defined the object of studies for American academia and set its research agenda. Not only has this presentation of Islam over politicized it, but it marginalized a plethora of significant traditional structures and concepts, as well as several modern responses that are not included in the brothers’ discourse. The overpoliticization of Islam and presenting it as necessarily Islamism has become not just a problem of media misrepresentation, but a crisis in the quality of knowledge about Islam that is produced and nurtured in academia. Moreover, this situation developed two unfortunate scholarships on modern Islam in Western academia that further distorted and blocked our knowledge on Islam: one is minor and Islamophobic, the other is major and Islamophilic. The Islamophobic approach sees Islam as inherently opposed to the modern structures of civil society, democracy, cultural diversity, and free market. The Islamophilic approach portrays Islamism—seen as the normative form of modern Islam, which is embraced by Muslim societies, as legitimate and popular native protest movement against non-democratic regimes. An exploration of John Esposito, whose scholarship has set the tone on Islam in academia for decades, and whose books have been widely adopted in courses taught in American universities will prove my argument.